ANALISIS HUKUM EKONOMI SYARIAH TERHADAP KEHALALAN PRODUK MAKANAN ONLINE TANPA SERTIFIKAT HALAL MUI - Amin Rais; Maimun Maimun; Abdul Qodir Zaelani; Liky Faizal (Universitas Muhammadiyah Surabaya, 2023)
This article aims to explain the results of the author's analysis of the implementation of halal certificates on food products sold online, inhibiting and supporting factors for the application of halal certificates to food sold online, and the impact of Sharia economic law on the haleness of food products sold online without halal certificates. The results of the 2021 survey on e-commerce statistics show that the types of goods and services sold the most online in Lampung are food and beverage groups, totaling 40.86 percent of all businesses sampled by e-commerce. The rapid progress of buying and selling food online has become an additional task for halal certificate implementation agencies in providing security and comfort, especially for Muslim consumers in Indonesia, so they can consume halal food that is traded online. The research methodology that the author uses is qualitative in terms of the type of research documentation, interviews, and observations. The author goes directly to the field to conduct observations and interviews with primary data derived from the results of interviews with the BPJPH task force and LPPOM MUI. The results of the study show that there are no special strategies for food sold online. Supporting factors include the existence of institutions assisting the halal product process for MSME business actors. The inhibiting factor is that there is no direct regulation of cooperation with online business application server managers, a lack of public understanding of halal certificates, Analysis of Sharia Economic Law on the haleness of food products sold online: the haleness of products sold online or offline without MUI halal certificates are categorized as syubhat. According to Imam Nawawi, doing syubhat is form of underestimating.the.law.without.realizing.that.they.have.done.haram.